Lesson Learned From Hospital Palliative Care Service in a Cancer Research Center in Italy: Results of 5 Years of Experience - Alquati, Sara; Peruselli, Carlo; Turrà, Caterina; Tanzi, Silvia (Frontiers in Oncology, 2022)
Background International studies have documented that over a third of all hospital beds are occupied by patients with palliative care needs in their last year of life. Experiences of Palliative Care Services that take place prevalently or exclusively in hospital settings are very few in Italy. Objective Describe clinical, educational and research activities performed by a hospital PCS and discussing opportunities and critical issues encountered in an Italian Cancer Center. Method Retrospective data regarding adults with advanced stage diseases referred from January 2015 to December 2019. Results Clinical activity - The PCS performed 2422 initial consultations with an average of 484 initial consultations per year. A majority of patients had advanced cancer, from 85% to 72%, with an average of 2583 total consultations per year and an average of 4.63 consultations per patient. The penetrance has increased over time from 6.3% to 15.75%. Educational and research activity - Since 2015, PCS has provided training to health professionals (HPs) of different departments of our hospital. Most of the educational projects for HPs were part of research projects, for example the communication training program, management of pain and end-of-life symptoms and the training program for PC-based skills. Conclusion Our data suggests that a PCS able to provide palliative care to inpatients and outpatient and continuous training support to other hospital specialists can relatively quickly improve the level of its penetrance in hospital activities.